Complete nucleotide sequences of two NDM-1-encoding plasmids from the same sequence type 11 Klebsiella pneumoniae strain - Studentova, V; Dobiasova, H; Hedlova, D; Dolejska, M; Papagiannitsis, C C; Hrabak, J (Antimicrobial agents and chemotherapy, 2015)
The sequence type 11 Klebsiella pneumoniae strain Kpn-3002cz was confirmed to harbor two NDM-1-encoding plasmids, pB-3002cz and pS-3002cz. pB-3002cz (97,649 bp) displayed extensive sequence similarity with the blaNDM-1-carrying plasmid pKPX-1. pS-3002cz (73,581 bp) was found to consist of an IncR-related sequence (13,535 bp) and a mosaic region (60,046 bp). A 40,233-bp sequence of pS-3002cz was identical to the mosaic region of pB-3002cz, indicating the en bloc acquisition of the NDM-1-encoding region from one plasmid by the other.
Keywords: Klebsiella pneumoniae; plazmidy; Plasmids; beta-laktamasy; beta-Lactamases